Juozas Gabrys and Lithuania at the League of Nations: Press, Business, Politics - Šipelytė, Monika (Lietuvos istorijos studijos, 2021)
The activity of Juozas Gabrys and his colleagues at the League of Nations in Geneva from 1927 until 1939 is the main subject of this article. The questions about this group of people are analyzed through several perspectives, such as journalism, business, and politics. The territorial and ethnical problems which were addressed by Lithuania at the League of Nations and the decisions of Lithuanian diplomats and politicians were overviewed in the press publications of Gabrys in various Lithuanian newspapers. In these texts he mostly focuses on two main topics in international interwar Lithuanian politics – the question of Vilnius its regarding mutual relations with Poland and the question of Memel and its region, which was intensely disputed by Lithuanian and German influences. Simultaneously, Gabrys had the intentions to develop business relations between Lithuania and Switzerland. He and his family worked in the fields of real estate and money exchange. Also, he established the Lithuanian Information Bureau in Geneva, which received irregular donations from the Lithuanian Ministry of Foreign Affairs, yet most of the publications were funded by Gabrys himself. The answer to the question of Gabrys’s real influence on Lithuanian foreign policy could be given only partially. As for now, the possibility to measure this influence is limited only to the press and information field, as Gabrys’s work in those fields, although forgotten and underestimated nowadays, was observed and evaluated by his contemporaries. Due to his publications, Lithuanians could form an opinion about the League of Nations and its decisions as well as the situation on the level of European policy.
Keywords: Juozas Gabrys; League of Nations; Geneva; interwar; diplomacy; journalism; press